Evaluasi Pengalaman Pengguna Pada Aplikasi E-Office Desa Menggunakan User Experience Questionnaire - Ginanjar, Ramdan; Supriadi, Fidi; Junaedi, Dani Indra; Agustino, Barkat (Yayasan Pendidikan Tanggui Baimbaian, 2024)
E-Office Desa is a web-based and mobile-based application that has been integrated for Village Apparatus within the Regional Government of Sumedang Regency which provides convenience in the administrative management process, one of which is correspondence. Based on the results of interviews with a number of village officials, they stated that this application was not entirely easy to use. Related to this, the form of testing from the aspect of convenience can use user experience methods, such as System Usability Scale (SUS), Software Usability Measurement Inventory (SUMI), Net Promote Score (NPS) and User Experience Questionnere (UEQ). SUMI, NPS, SUS methods have shortcomings when assessing the perception of user subjectivity and deep insight, while these problems can be overcome by the UEQ method. Evaluation of user experience testing is done to see how satisfied the user experience is when using the village e-office application. This research focuses on the use of the Village E-Office application in Cibugel Sub-district because based on data, mail management services are still below other sub-districts, which is around 2,689 letters for 4 years. The obtained values for each aspect of UEQ are attractiveness 1.577, Perspicuity 1.822, efficiency 1.684, Dependability 1.597, stimulation 1.591 and novelty 1.581. This shows that all aspects of user experience get a positive impression with the UEQ method. The results of this study can be used as recommendations for future user experience improvements by innovating in various aspects.